Disaster globalization: Evaluating the impact of tsunami aid - Walker, Peter (Tufts Archival Research Center, 2005)
The tsunami and earthquakes that hit the Indian Ocean 26th December 2004 caused a disaster so extreme and so unusual that it pushed all our models of response to the limit.